GAME FOR TEACHING REHABILITATION TO THE PERSON UNDERGOING HIP ARTHROPLASTY: CASE STUDY - Carla Sílvia Fernandes; Andreia Elisabete Soares; Catarina Amaral; Eva França Costa; Inês Silva Santos Almeida; Pedro Manuel Ascensão Nogueira (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Objective: The study aimed to know the opinion of students specializing in rehabilitation nursing in the context of clinical teaching on the use of a Game to teach rehabilitation care to the person undergoing Hip Arthroplasty. Methodology: This is a multiple, descriptive and exploratory case study, in which the game Reabilit´Arte was developed and applied. Participants were selected through snowball sampling. For data collection, a brief sociodemographic characterization, application of the Training Strategy Assessment Instrument (IAEF), and open questions about the advantages and disadvantages of the game were carried out. Atlas-ti version 8.0 software was used to analyze open questions. Results: The sample consisted of 9 postgraduate students in rehabilitation nursing. Regarding the evaluation of the use of the game, it is observed that, on average, the application of the full scale values varied between 80 and 100, much above the average value of the scale. From the data analysis, the subcategories emerged within the scope of the advantages of the game: reinforcement of teaching, ease of learning, active participation, motivation and visual memory. In terms of disadvantages, the time factor and the characteristics of the participants are presented less frequently. Conclusion: The game was positively evaluated, revealing that the intervention of the specialist nurse in rehabilitation nursing through a game can be useful to promote adaptive capacities with a view to self-control and self-care in the transition processes of health / disease and or disability.